Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,35:\left(\frac{-5}{3}\right)+2\frac{1}{2}:\left(-\frac{5}{3}\right)=35.\left(-\frac{3}{5}\right)+\frac{5}{2}.\left(-\frac{3}{5}\right)\)
\(=-21+-\frac{3}{2}\)
\(=\frac{-42-3}{2}=-\frac{45}{2}\)
\(b,\frac{10^3+2.5^3+5^3}{55}=\frac{\left(2.5\right)^3+2.5^3+5^3}{5.11}\)
\(=\frac{5^3\left(2^3+2+1\right)}{5.11}\)
\(=\frac{5^2\left(8+2+1\right)}{11}\)
\(=\frac{5^2.11}{11}=5^2=25\)
\(C,\frac{27^2.2^5}{6^6.32^3}=\frac{\left(3^3\right)^2.2^5}{\left(2.3\right)^6.2^5}\)
\(=\frac{3^6}{2^6.3^6}=\frac{1}{2^6}=\frac{1}{64}\)
\(\left(-\frac{10}{3}\right)^5.\left(-\frac{6}{5}\right)^4=\frac{\left(-10\right)^5}{\left(-3\right)^5}.\frac{\left(-6\right)^4}{\left(-5\right)^4}=\frac{\left(-5\right)^4.\left(-5\right).\left(-2\right)^5}{\left(-3\right)^4.\left(-3\right)}.\frac{\left(-3\right)^4.\left(-2\right)^4}{\left(-5\right)^4}=\frac{\left(-5\right).\left(-2\right)^5.\left(-2\right)^4}{\left(-3\right)}\)
\(=\frac{\left(-5\right).\left(-2\right)^9}{\left(-3\right)}\)
B1:
a)x=-3/5*9/25 =>x=-27/125
b)x=(4/7)6:(4/7)4 =>x=(4/7)2=16/49
c)(x/4)2=4:(x/2)
(x/4)2=8/x
x2/16=8/x2
x3=128
x=5,039
B2
M=23.10+22.10/23.4+22.11
=230+220/212+222
=230+28+222
=28(222+1+214)
=2
\(S=\left(2.1\right)^2+\left(2.2\right)^2+\left(2.3\right)^2+....+\left(2.10\right)^2\)
\(\Rightarrow S=2^2.1^2+2^2.2^2+....+2^2.10^2\)
\(\Rightarrow S=2^2\left(1^2+2^3+3^2+.....+10^2\right)\)
Áp dụng giả thiết từ đề
\(\Rightarrow S=2^2.385\)
\(\Rightarrow S=4.384=1540\)
\(S=2^2+4^2+6^2+...+20^2\)
\(=1^2.4+2^2.4+3^2.4+...+10^2.4\)
\(=4.\left(1^2+2^2+3^2+...+10^2\right)\)
\(=4.385=1540\)
\(\left(\frac{1}{16}\right)^{10}\) và \(\left(\frac{1}{2}\right)^{50}\)
Ta có: \(\left(\frac{1}{2}\right)^{50}=\left[\left(\frac{1}{2}\right)^5\right]^{10}=\left(\frac{1}{32}\right)^{10}\)
Do \(\frac{1}{6}>\frac{1}{32}\Rightarrow\left(\frac{1}{6}\right)^{10}>\left(\frac{1}{32}\right)^{10}\)
Vậy \(\left(\frac{1}{16}\right)^{10}>\left(\frac{1}{2}\right)^{50}\)
a) \(10^{20}\) và \(9^{10}\)
Vì 10 > 9 ; 20 > 10
nên \(10^{20}>9^{10}\)
Vậy \(10^{20}>9^{10}\)
b) \(\left(-5\right)^{30}\) và \(\left(-3\right)^{50}\)
Ta có: \(\left(-5\right)^{30}=5^{30}=\left(5^3\right)^{10}=125^{10}\)
\(\left(-3\right)^{50}=3^{50}=\left(3^5\right)^{10}=243^{10}\)
Vì 243 > 125 nên \(125^{10}< 243^{10}\)
Vậy \(\left(-5\right)^{30}< \left(-3\right)^{50}\)
c) \(64^8\) và \(16^{12}\)
Ta có: \(64^8=\left(4^3\right)^8=4^{24}\)
\(16^{12}=\left(4^2\right)^{12}=4^{24}\)
Vậy \(64^8=16^{12}\left(=4^{24}\right)\)
d) \(\left(\frac{1}{6}\right)^{10}\) và \(\left(\frac{1}{2}\right)^{50}\)
Ta có: \(\left(\frac{1}{6}\right)^{10}=\left[\left(\frac{1}{2}\right)^4\right]^{10}=\left(\frac{1}{2}\right)^{40}\)
Vì 40 < 50 nên \(\left(\frac{1}{2}\right)^{40}< \left(\frac{1}{2}\right)^{50}\)
Vậy \(\left(\frac{1}{16}\right)^{10}< \left(\frac{1}{2}\right)^{50}\)
\(\frac{10^3+2.5^3+5^3}{55}\)
\(=\frac{5^3+\left(2^3+2+1\right)}{55}\)
\(=\frac{5^3.11}{5.11}\)
\(=5^2=25\)
ta có đề bài
\(=\frac{2^3.5^3+2.5^3+5^3}{5.11}=\frac{5^3\left(2^3+2+1\right)}{5.11}\) \(=\frac{5^3.11}{5.11}=5^2=25\)